The Effect of Educational Videos on the Driving Safety and Health Behavioral Domain of Drivers in PERUM DAMRI Bus Yogyakarta - Arthamevia, Salsabila Prama; Zulhayudin, Muhammad Fadillah (Periodicals of Occupational Safety and Health, 2025)
Background: Traffic accidents remain one of the leading causes of death in Indonesia, especially in public transportation sectors such as buses. Human error, influenced by a lack of knowledge and awareness regarding Occupational Safety and Health (OSH), plays a major role. Preventive efforts such as OSH promotion using engaging and educational video media are needed to reduce accident rates and increase driver safety. Method: This study employed a quasi-experimental method using a nonequivalent control group design. The population consisted of 63 bus drivers from Perum DAMRI Yogyakarta, divided into an experimental group (31) and a control group (32). The research instrument used structured pretest and posttest questionnaires to assess knowledge and attitude. Data were analyzed using Paired Sample t-Test and Independent t-Test. Results: The results showed a significant improvement in the knowledge and attitudes of the experimental group after the intervention. The Paired Sample t-Test indicated a significant increase in knowledge (p=0.000) and attitude (p=0.000). Furthermore, the Independent t-Test showed significant differences between the experimental and control groups in both knowledge (p=0.001) and attitude (p=0.002). Conclusion: The educational video on bus driving safety had a significant positive impact on improving the OSH behavioral domain, specifically knowledge and attitudes, among Perum DAMRI drivers in Yogyakarta. This media can serve as an effective tool for safety promotion and accident prevention in the transportation sector.